Evaluating the potential of anti-dsRNA antibodies as an alternative viral sensing tool in encephalitides of different species - de le Roi, Madeleine; Gerhards, Hannah; Fayyad, Adnan; Boelke, Mathias; Becker, Stefanie Christine; Volz, Asisa; Gerhauser, Ingo; Baumgärtner, Wolfgang; Puff, Christina (Frontiers in Veterinary Science, 2025)
Although laboratory methods have advanced, the cause of many encephalitides is still unknown. Molecular methods like multiplex PCR and microarrays are considered to be often less sensitive than Next Generation Sequencing, whereas the latter is time-consuming and costly. These analyses require appropriate tissue preparations and are more difficult to perform on formalin-fixed, paraffin-embedded (FFPE) tissues. Anti-double-stranded RNA (dsRNA) antibodies could potentially identify virus infections independently of the viral genome and can be applied to FFPE material. This study examined the applicability of monoclonal anti-dsRNA antibodies by immunohistochemistry to confirm encephalitides caused by different RNA viruses and comparing the findings with those obtained using monoclonal and polyclonal virus-specific antibodies. The viruses studied included negative-sense (Borna disease virus 1, BoDV-1; canine distemper virus, CDV; Rift Valley fever virus, RVFV) and positive-sense single stranded RNA viruses (severe acute respiratory disease syndrome coronavirus 2, SARS-CoV-2; tick-borne encephalitis virus, TBEV; Theiler’s murine encephalomyelitis virus, TMEV). Interestingly, dsRNA was detected in both infected and non-infected animals and inconsistently co-localized to BoDV-1, TBEV, and TMEV antigen. Strict co-localization was lacking in CDV, SARS-CoV-2 and RVFV. Despite the co-localization of dsRNA with virus antigen for some RNA viruses, anti-dsRNA antibodies were unreliable as markers for unknown virus infections. Future studies should explore the upstream components of the immune response, including the interferon signaling cascade to assess their potential as effective virus-sensing tool.